2000
DOI: 10.1046/j.1365-2036.2000.014s2062.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: gall‐bladder motor function in diabetes mellitus

Abstract: Although some controversy exists, diabetic patients generally are thought to have a two-to threefold increased risk of cholesterol gallstones. From previous studies there is no convincing evidence for a supersaturated bile in diabetics, whereas several reports indicate that impaired gall-bladder emptying could be one of the important factors in the increased incidence of gallstones in diabetics. However, studies of gall-bladder motility in diabetics have yielded con¯icting results, probably because of substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
2
17
3
Order By: Relevance
“…In patients with T2DM, who were characterised by massive glucagon hypersecretion, nutrient composition in meals did not give rise to different glucagon profiles, suggesting that meal calories rather than composition is the prime regulator of postprandial glucagon secretion in patients with T2DM. Our observation of preserved gallbladder emptying in patients with T2DM is in contrast to the majority of studies of gallbladder function in T2DM (17,18,19). However, some studies report preserved gallbladder emptying, but deviate from this study in terms of patient selection, control group, methods of investigation and stimuli used for inducing gallbladder contraction (17,45).…”
Section: European Journal Of Endocrinologycontrasting
confidence: 53%
See 2 more Smart Citations
“…In patients with T2DM, who were characterised by massive glucagon hypersecretion, nutrient composition in meals did not give rise to different glucagon profiles, suggesting that meal calories rather than composition is the prime regulator of postprandial glucagon secretion in patients with T2DM. Our observation of preserved gallbladder emptying in patients with T2DM is in contrast to the majority of studies of gallbladder function in T2DM (17,18,19). However, some studies report preserved gallbladder emptying, but deviate from this study in terms of patient selection, control group, methods of investigation and stimuli used for inducing gallbladder contraction (17,45).…”
Section: European Journal Of Endocrinologycontrasting
confidence: 53%
“…Our observation of preserved gallbladder emptying in patients with T2DM is in contrast to the majority of studies of gallbladder function in T2DM (17,18,19). However, some studies report preserved gallbladder emptying, but deviate from this study in terms of patient selection, control group, methods of investigation and stimuli used for inducing gallbladder contraction (17,45). To provide an explanation for this disparity, it is relevant to review our selection of patients with T2DM.…”
Section: European Journal Of Endocrinologycontrasting
confidence: 48%
See 1 more Smart Citation
“…In a study done by Raman et [12] it was shown that percentage contraction of gallbladder was reduced in diabetes with gallbladder disease (41.84±11.74%) as compared to controls (53.07±16.31 %) and diabetics without gallbladder disease (48.74±11.75%). Similar findings were produced by Gaur et al, [7] Pazzi et al, [14] Yang et al [11] and Kayacetin et al [15] Thus the present study was clearly in concert with the above mentioned studies.…”
Section: Gallbladder Diseasesupporting
confidence: 81%
“…Stone et al [13] demonstrated impaired gallbladder emptying in diabetics with autonomic neuropathy. Pazzi et al [14] in their study implicated visceral neuropathy to be the cause of reduced gallbladder motility. According to Gaur et al [7] gallbladder volumes were significantly larger in patients of diabetes mellitus and these values were significant in those with autonomic neuropathy.…”
Section: Autonomic Neuropathymentioning
confidence: 99%